Disparity in Quality of Infectious Disease vs Addiction Care Among Patients With Injection Drug Use–Associated Staphylococcus aureus Bacteremia. (18th June 2019) - Serota, David Phillip; Niehaus, Emily D; Schechter, Marcos C; Jacob, Jesse T; Jones, Jeb; Ray, Susan M; Kelley, Colleen F; Kempker, Russell R
Abstract: Evidence-based interventions for Staphylococcus aureus bacteremia (SAB) are well known, but it is unclear how they are implemented among patients with injection drug use–associated (IDU) SAB. Of 46 patients with IDU-SAB identified, all received high-quality SAB management; however, few received appropriate recognition or treatment of their underlying substance use disorder.